Kemiskinan dan kondisi pemukiman nelayan tradisional (studi di Kelurahan Kampung Nelayan Kecamatan Tungkal Ilir Kabupaten Tanjung Jabung Barat) - Nurhayani Nurhayani; Siti Hodijah (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
This study aims to analyze the poverty problems of traditional fishermen at Nelayan Village Tungkal Ilir District, Tanjung Jabung Barat Regency. And analyze the condition of coastal settlements of traditional fishing communities at Nelayan Village Tungkal Ilir District, Tanjung Jabung Barat Regency. The poverty that occurs in traditional fishermen at Nelayan Village is caused by 3 (three) most influential factors. There are; 1) quality factor of human resources, 2) economic factor, and 3) institutional factor. The spread pattern of settlements of traditional fishing communities at Nelayan Village takes place naturally, spontaneously and tend to be sporadic. This fishing community settlement tends to be dense